Utilization Of Crude From Part Of Kepok Banana Trees With Maceration Extraction As Textile Colors - Wahidin Nuriana; Marti Winarni (Agroindustrial Technology Journal, 2020)
The purpose of this study was to obtain a natural textile dye taken from the sap from the banana tree part. To obtain the yield yield of dyes and the intensity of the sap collection isdone by maceration extraction process. The part of the banana tree taken by the sap is the stem, stem and fruit stalk. This research was conducted with the sorting stage, namely thinly slicing stems, midribs and fruit stalks. The results of sorting are dried in the sun for 5 days in the sun then crushed until smooth with a size of 60-80 mesh. The powder was extracted by maceration by immersing each stem, stem and fruit stalk with soaking media: aquades, methanol, ethanol and ethyl acetate for 5 days with manual stirring. The filtrate is distilled so that it gets concentrated liquid and in the oven to become a dye powder. In the powder, yield and color testing are done using a spectrophotometerUV Vis. The most optimal yield produced is on the banana fronds with methanol mediais 22.8248%.. The optimal color intensity was obtained on banana stalks using methanol maceration medium and methanol dilution is 0.505